Roman Catholic Government and Mission to Tibet: A Historical and Theological Study - Beltramini, Enrico (International bulletin of mission research, 2021)
In this article I consider the administration of the Roman Catholic Church mission to Tibet in the seventeenth and eighteenth centuries. After summarizing the main events of this mission, I focus on the juridical-political aspects of the government (i.e., administration) of mission. I contribute to the understanding of the history of mission to Tibet by addressing administration in theological terms. I show that government in the history of mission to Tibet cannot be seen merely through the lens of politics (bureaucracy, etc.) but as an activity that is a significant element in the economy of salvation.